The psychosocial factors associated with work stress among inpatient psychiatric nurses at RSJD Dr. Amino Gondohutomo Semarang: A cross-sectional study - Winerti, Hanisha; Ardyanto Wahyudino, Yustinus Denny; Wahyuni, Ida; Jayanti, Siswi (University of Muhammadiyah Malang, 2026)
Introduction: Nurses in psychiatric inpatient wards must remain highly alert because patient behavior can be unpredictable and potentially risky. Despite the demanding work environment, research on psychosocial factors associated with work stress among psychiatric nurses remains limited in Southeast Asia and other low- and middle-income countries (LMICs).Objectives: This study aims to determine the relationships among mental workload, colleague support, and work shifts with work stress among female nurses working in the psychiatric inpatient ward at RSJD Dr. Amino Gondohutomo Semarang.Methods: This quantitative analytic study used a cross-sectional study design. The population consisted of 111 female psychiatric inpatient nurses, and 60 respondents were selected through proportional sampling. Data were collected using structured questionnaires and analyzed using chi-square tests.Results: Of the respondents, 38.3% experienced mild work stress, 51.7% reported low coworker support, and 38.4% had low mental workload. Nurses who frequently worked evening or night shifts reported a higher proportion of work stress than those on regular shifts. Significant associations were found between mental workload (p=0.008), coworker support (p=0.002), and shift work (p=0.043) and work stress.Conclusion: Work stress among psychiatric nurses is shaped by workload, peer support, and shift patterns, underscoring the need for a comprehensive psychosocial approach. Beyond individual coping strategies, such as maintaining adequate rest, organizational measures are essential to reduce work stress and enhance the quality of psychiatric nursing services. These measures include optimizing shift schedules, strengthening peer support, and ensuring adequate staffing.